APPLICATION OF ANT COLONY OPTIMIZATION ALGORITHM ON DETERMINATION OF TRANSPORTATION FROM BELAWAN TO TUNTUNGAN CAMPUS - Juliana; Juliani; Ramadhani, Akhiriyah; Widya, Ade; Farhan Zacky, M. (Journal of Mathematics and Scientific Computing With Applications, 2024)
Transportation is an alternative used by everyone to get to a destination. In research, several alternative means of transportation can be used by students who live far from their campus. Students can determine the closest route to get to their campus. The campus we take is UINSU Campus IV. This research aims to overcome the transportation problems of students who live in the Belawan area and its surroundings. The research also used the ant colony optimization (ACO) algorithm method, with this method to make it easier to get the shortest route with a short time and the lowest cost or still standard with the distance. The ant colony optimization method is an algorithm inspired by the natural life of ants regarding ant habits in finding food. This research aims to get the shortest route and the optimal means of transportation used. In this study, it was found that the optimal means of transportation as well as distance, time, and cost were motorcycle transportation with a distance of 64.5km and the time required was 1 hour 4 minutes and the cost to be incurred was Rp. 40,000.00. This research uses Google Maps data to determine the distance of a location. Although the results are not optimal, it can be used as a solution for students in calculating the distance, time and cost to be used.